Pretoria Student Law Review 2015 - 9 - Alexia Katsiginis (Pretoria University Law Press (PULP), 2016)
About the publication Words fail to describe what an honour it has been to have been part of the ninth edition of the Pretoria Student Law Review. The sense of satisfaction is overwhelming in this being the third edition I have had the privilege to be a part of. Having spent three years as part of this publication I cannot begin to describe and expand upon all that I have learnt in this time, but one thing which I guarantee is the bright and prosperous future of the legal profession of South Africa. With each successive edition I see a thirst and hunger for knowledge from law students, each year those yearnings becoming more intense and providing us with the most thought provoking and well-founded articles. The desire to challenge the status quo, to reject the notions of complacency and outright refusal of facile thought is truly something all these writers should be proud of and us along with them. To read and to write is the essence of not only thought, but of life itself. Editor in chief: Alicia Allison Editors: Alexia Katsiginis and Michael Potter Table of Contents Editors' note Alicia Allison From the Dean's desk Andre Boraine Challenges to peaceful protest in Nigeria: The use of force Adebayo Okeowo (Wo)man in the mirror - A reflection: Law's influence on society, identity and feminism Devon-Lee Andries The impossibility to be lost in transformation JJ van der Walt The political constructions of justice: Reviewing Antjie Krog's Country of my skull and application of African jurisprudence Marko Svicevic The effect of the South African media on HIV/AIDS awareness Nicole King A new 'ray of light' in socio-economic rights jurisprudence? A note on Coughlan NO v Road Accident Fund (Centre for Child Law Amicus Curiae) (CCT160/14) [2015] ZACC 9 Romy-Anne Templeton The 'irrational' female was invented by the patriarchal society Sarah Hartman Liability in space law: Questions on practical application of absolute fault and liability Sevela Masie & Kaitlin Morris Introducing deconstructive intersectionality: The general jurisprudential rage against rainbow theory Tamryn Gordon